Implementation and Performance Analysis of Private Cloud Using Openstack Swift and Rclone - Aditama, Candra; Priadana, Adri (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2019)
Many companies need a storage system that can be accessed in real time by all parts of the company. Most digital data storage methods today still use conventional methods where data is stored on an external hard disk or public cloud. Storage with external hard disk media makes accessing data difficult and has the risk of data loss when storage media is damaged. On the other hand, the storage method using public cloud requires an internet connection with large bandwidth requirements and the company still has to spend a budget on renting it. This study aims to design digital data storage methods using a private cloud that can be accessed in real time by all parts of the company without having to spend a budget on hiring a storage media and renting an internet connection with large bandwidth requirements. A private cloud was built using OpenStack Swift as an object storage service provider and Rclone as a cross-platform computer data management application. The results of this study are the creation of a private cloud that runs object storage services using Swift storage objects with relatively light and high scalability to meet the needs of storing data effectively and efficiently. A private cloud-based data storage media with relatively light and high scalability to meet data storage needs. Data storage media that can be accessed easily without having to use an internet connection with large bandwidth requirements.